Refractory solitary cervical lymph node metastasis after esophageal squamous cell carcinoma surgery and its successful treatment with immune checkpoint inhibitor: A case report and literature review. Issue 10 (March 2020) - Song, Wenjing; Wang, Helei; Tian, Yuanyuan; Liu, Shiwei; Chen, Xiao; Cui, Jiuwei; Zhao, Yuguang
Abstract: Rationale: Although the early detection and treatment of non-metastatic esophageal cancer has improved, these patients' prognoses are still poor. Most patients with radical treatment for esophageal cancer will relapse in 3 years, and the best treatment strategy after recurrence has not been uniformly accepted. Multiform treatments may be beneficial to recurrent patients. Patient concerns: A 60-year-old male patient, due to routinely health examination, ulcerated lesions 30 cm away from the incisors were found by gastroscopy, pathology showed esophageal squamous cell carcinoma (ESCC). Diagnosis: Due to the patient's pathology, he was diagnosed with ESCC. Interventions: The patient underwent radical surgery for ESCC on June 28, 2015. The left cervical lymph node metastasis occurred after 20 months, and lymph node metastasis carcinoma resection was performed. After that, concurrent chemoradiotherapy was implemented, 40 days after the end of the 4 courses of chemotherapy, the left cervical metastatic lymph nodes relapsed, radioactive particle implantation was carried out, and progressed again after 1 month. The patient took apatinib for 1 week but could not tolerate due to hand-foot syndrome. Immune checkpoint inhibitor (ICI) was administered since October 27, 2017. Outcomes: The therapeutic effect of immune checkpoint inhibitor was evaluated as partial response (PR) after 6 courses of treatment and complete response (CR) after 15 courses of treatment. To our knowledge, this is the first case report of successful immunotherapy for refractory esophageal squamous cell carcinoma. Lessons: The emergence of ICIs promotes the treatment of esophageal cancer to a new era. Our observations suggest that patients for whom schedule to receive anti-programmed cell death protein-1 (anti-PD-1)/programmed cell death-ligand 1 (PD-L1) immunotherapy may require genomic testing to predict whether tumors respond to ICIs. In this case, we also present the predictors for the efficacy of targeted immunotherapy. At present, no matter which predictor of PD-L1 expression, tumor mutational burden (TMB), microsatellite instability (MSI), and tumor-infiltrating lymphocyte (TIL), a single predictor may be unconvincing and cannot accurately estimate the efficacy of immunotherapy. Multiplex detecting methods and combined biomarkers may provide new strategies. Consensus need to be reached in order to be widely applied in future studies.